2018
DOI: 10.3892/ol.2018.9447
|View full text |Cite
|
Sign up to set email alerts
|

Analyses and treatment of simultaneous bi‑lineage malignancies of myeloid leukemia and lymphoma: Two case reports and a literature review

Abstract: The present study reports two cases of concurrently diagnosed T-lymphoblastic lymphoma (T-LBL) and chronic myeloid leukemia (CML). The literature review revealed that myeloid leukemia may appear secondary to Hodgkin lymphoma or non-Hodgkin lymphoma. However, simultaneous bi-lineage hematologic malignancies are rarely seen and the prognosis is worse than single lineage lymphoma or myeloid leukemia. There were no standard therapies. All simultaneous bi-lineage malignancies of myeloid leukemia and lymphoma report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Differential diagnoses of lymphadenopathy associated with CML include infection (tuberculosis...), myeloid proliferation (myeloid sarcoma/chloroma), Hodgkin lymphoma (HL), non-Hodgkin lymphoma (NHL) B/T, and lymphoblastic lymphoma B/T-LBL [ 13 ]. The prognosis of blast crisis and EBC is very poor [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential diagnoses of lymphadenopathy associated with CML include infection (tuberculosis...), myeloid proliferation (myeloid sarcoma/chloroma), Hodgkin lymphoma (HL), non-Hodgkin lymphoma (NHL) B/T, and lymphoblastic lymphoma B/T-LBL [ 13 ]. The prognosis of blast crisis and EBC is very poor [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective case series of patients with bi-lineage myeloid and lymphoid neoplasms, hematopoietic stem cell transplantation (HSCT) resulted in a statistically significant advantage in overall survival [ 13 ]. Allo-SCT is associated with a high rate of transplantation-related mortality [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a case report of secondary malignancies in CML [ 7 ]. Fu et al [ 8 ] reported simultaneous diagnosis of T-LBL and BCR-ABL positive CML in two adult patients who were treated with imatinib and HYPER-CVAD chemotherapy. Simultaneous acute myeloid leukaemia (AML) and lymphoma has been reported in the literature and is more frequent than simultaneous CML and lymphoma [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ils sont responsables du développement de tumeurs au niveau des organes lymphoïdes, notamment ganglionnaires, mais aussi de territoires non lymphoïdes (Cuenca et al, 2009). La coexistence d'une double prolifération maligne, myéloïde et lymphoïde et particulièrement lymphomateuse, est rare bien que décrite depuis quelques décennies (Martoïa et al, 1987;Doumouchel et al, 1983;Monoharan et al, 1981) et depuis quelques années plusieurs publications décrivent des hémopathies lymphoïdes diversement associées aux hémopathies myéloïdes surtout la LMC (Amy et al, 2018; Xiaorui Fu et al, 2018;Paolo et al, 2018;Smeeta Gajendra et al, 2016). Cette coexistence qu'elle soit spontanée ou non, simultanée ou séquentielle, elle évoque davantage une atteinte de la cellule souche hématopoïétique, se démasquant au niveau de deux lignées filles, qu'une banale coïncidence.…”
Section: Introductionunclassified